Sosialisasi dan Pelatihan Penggunaan Pupuk Agens Hayati Mikoriza - Tholib Hariono; Mohamad Nasirudin; Indah Fitriani; Abdul Latif (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
The purpose of this service program is to socialize mycorrhizal biological agent fertilizers to residents in order to restore soil fertility, reduce crop yields that contain chemicals, take advantage of what nature has provided, efficiency of nutrient and water absorption. The approach method for implementing community service activities in this Socialisani scheme includes lectures, discussions, and workshops (training) methods. Based on the results of community service activities, it can be concluded as follows; Provide additional insight and knowledge and skills to Banjarsari Farmers about Mycorrhizal Biological Agent Fertilizer and the negative impact of continuous use of Chemical Fertilizer. Helping Banjarsari Farmers on how to apply Mycorrhizal Biological Agent Fertilizer and how to propagate it, Providing Farmers Solutions in the midst of the shortage of subsidized chemical fertilizers.